Genomic data, effective communication through visualization - Malinda, Raj Rajeshwar; Mishra, Dipika (Acta Biologica Szegediensis, 2025)
Genomic data are inherently multidimensional and complex, therefore, presenting researchers with significant challenges in analysis and interpretation. Data visualization of genomic datasets can unravel the complexity and provide meaningful insights for effective communication. Here, we discuss that, in data-driven genomic studies, effective storytelling of formulated hypotheses can be significantly enhanced by using suitable data visualization tools. Further, with the ongoing advancement of technology, we argue that, the integration of these tools with artificial intelligence or machine learning concepts could potentially revolutionize the visualization trends within the field of genomic research.